Means-end chain theory applied to Irish convenience food consumers - De Boer M.; McCarthy M.B. (Food quality products in the advent of the 21st century: production, demand and public policy, 2005)
This study focuses on two food-related lifestyle consumer segments that were identified as high frequency purchasers of convenience foods on the Irish market; the hedonistic and the adventurous consumer segments. The objective of this study was to get an understanding of how these consumers relate a distinctive attribute of convenience food, i.e. prepared, to obtaining higher order values in life. Twenty individual interviews, applying the laddering technique, were conducted in summer 2002. Means-end chains were explored for both segments. Results revealed that the values attained by the consumption of prepared food were very similar for both segments. However, some differences occurred in the motivational cognitive networks leading from the attribute 'prepared' to the end values. Both segments associated prepared food positively with feeling good about themselves & relaxing and family happiness, and negatively with family's health, wellbeing and security. For the hedonistic consumer, consequences preceding the positive values were saving time, convenience, flexibility, having a treat, and limiting waste of food. For the adventurous consumer prepared foods were viewed as saving time, convenience, flexibility, and variety in the daily meal pattern. With respect to family's health, wellbeing and security, the hedonistic consumer had concerns about prepared foods being bad for the family's weight control, while the adventurous consumer had doubts about the quality of ingredients in prepared food.
83. EAAE Seminar on Food Quality Products in the Advent of the 21st Century: Production, Demand and Public Policy, 2003/09/04-07, Chania (Greece)